Articles of the Mejelle on Istisna contract: juristic evaluation and applications - Rahman, Md. Habibur; Amanullah, Muhammad (UNiversity of Malaya, 2019)
The Majallat al-Aḥkām al-‘Adliyyah, known as the Mejelle, is the code of Islamic civil transactions which was prepared under the auspices of the Ottoman Caliphate. This code was established based on the Ḥanafī School of Islamic law. The paper intends to conduct a juristic evaluation of the articles of the Mejelle on istiṣnā‘ contract along with an investigation of its contemporary applications. Istiṣnā‘ is a contract to buy for a definite price something that may be manufactured later, under agreed specifications between contracting parties. The study finds that although articles of the Mejelle on istiṣnā‘ are known to be based on the Ḥanafī School, they generally are not contrary to the views of the majority of the Schools of Islamic law. It concludes that the contract of istiṣnā‘ is applicable as a modern tool to finance infrastructure development, high technology industries, and mega projects like highway construction, aircraft industries, locomotive, shipbuilding, and so forth.